Falling Sperm Counts in the Past 40 Years among Western Men: A Review Article (Journal of Comilla Medical College Teachers' Association, 2024)
Background: Recently so many studies have documented a concerning decline in semen quality among men in Western countries over the past few decades. This decline, characterized by reduced sperm concentration, motility and morphology, has been linked to a range of potential factors. Lifestyle changes, such as increased obesity rates, sedentary lifestyle and exposure to environmental pollutants are believed to contribute significantly. Additionally, factors such as poor diet, high levels of stress and exposure to endocrine disrupting chemical may also play a role. This deterioration in semen quality raises a concern about male infertility. The purpose of this review is to address the main disorders of semen quality, its aetiologies and steps which are essential to overcome the issues. Further research is crucial to fully understand the underlying mechanisms and to develop strategies to mitigate the impact of low quality semen on the reproductive health.J Com Med Col Teachers Asso July 2024; 28(2): 96-99